Blood Lipid Parameters In Populations of Russia, Poland And Czech Republic: The Hapiee Study - Nikitin, Yu P; Makarenkova, K V; Malyutina, S K; Pajak, A; Kubinova, R; Peasey, A; Bobak, M (Kardiologiia, 2015)
PURPOSE: to analyze population values of blood lipid parameters in general populations of Russia, Poland and Czech Republic. MATERIALS AND METHODS: In the frame of international project HAPIEE representative samples of general population were examined in Novosibirsk (Russia), Krakow (Poland) and six centers in the Czech Republic. The analysis included data of 25,469 men and women aged 45-69 years old. RESULTS: The average levels of total cholesterol (TC), non-high density lipoprotein cholesterol (non-HDL-C) and low density lipoprotein cholesterol (LDL-C) were found relatively high in all centers, though average levels of blood triglycerides (TG) and high-density lipoprotein (HDL) were within "normal" range. In Novosibirsk mean levels of blood TC and LDL-C in persons of both sexes were obtained the highest among the study participants: 6.3 mmol/ and 4.1 mmol/l, respectively (p < 0.001). But the level of blood triglycerides (1.5 mmol/l) in Novosibirsk was the lowest, and HDL-C (1.5 mmol/l) was the highest among three centres. There were clear trend of increasing concentration of blood TC, non-HDL-C,LDL-C and blood atherogenic indexes with increasing age in both sexes of all participating countries. In Czech Republic levels of blood TC, LDL-C, HDL-C in both sexes were relatively low: 5.7 mmol/l, 3.5 mmol/l, 1.4 mmol/l, respectively, but the level of blood TG were higher, than in other centers (1.9 mmol/l). Women of all centers had more demonstrative age changes of the blood lipid profile, than men. CONCLUSIONS: The average levels of blood TC, non-HDL-C and LDL-C in men and women aged 45-69 years old in Russia (Novosibirsk) were higher and level of blood TG was lower than in Poland and the Czech Republic.
Keywords: surveillance populace; Humans; lidé středního věku; následné studie; Female; Aged; Polsko; dyslipidemie; lipidy; morbidita; senioři; lidé; Poland; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Morbidity; Czech Republic; Rusko; Lipids; Russia; retrospektivní studie; Population Surveillance; Dyslipidemias; Česká republika; mužské pohlaví; Follow-Up Studies